Optimal management in optic nerve sheath meningioma – A multicentre study and pooled data analysis. (October 2020) - Ovens, Christopher; Dean, Benjamin; Gzell, Cecelia; Patanjali, Nitya; Jonker, Benjamin; O'Connor, Michael; Estoesta, Patrick; DeMartin, Tatiana; Fraser, Clare
Highlights: Primary optic nerve sheath meningiomas (ONSM) respond best to radiotherapy. Visual fields are the most sensitive marker of response to treatment in ONSM. 3D conformal radiotherapy confers poorer visual outcomes in ONSM. 3D conformal radiotherapy has more side effects than other radiotherapy types. Stereotactic radiosurgery offers equivalent visual outcomes with fewer side effects. Abstract: Optic nerve sheath meningiomas (ONSMs) are rare, benign neoplasms of the anterior visual pathway. The optimal modality of radiotherapy for treatment has not yet been established. This is the first study to show significant difference in visual outcomes between radiotherapy subtypes in the management of ONSM. We performed a retrospective analysis of visual outcomes and side effects in ONSM patients treated with radiotherapy at three centres in Sydney, Australia, between 2000 and 2016. 15 patients with ONSM were included, and visual outcomes (visual acuity, visual fields, colour vision, OCT retinal nerve fibre layer thickness and radiological tumour response) and treatment toxicities were assessed. Pooled data analysis of available studies was also performed. Statistical analysis was performed with binomial, two-tailed chi-squared tests and Fisher exact tests. In our cohort a significant majority experienced improved visual field (p = 0.046), stable or improved visual acuity (p = 0.0017) and colour vision (p = 0.015) after fractionated radiotherapy. Pooled analysis with strict inclusion criteria found 3D conformal radiotherapy to offer significantly poorer visual acuity compared to fractionated stereotactic radiotherapy (p = 0.008). When all published studies were included, stereotactic radiosurgery was superior to 3D conformal methods (p = 0.035), and equivalent to other fractionated methods. 3D conformal methods also had significantly higher rates of long-term side effects. These results support the use of fractionated radiotherapy and radiosurgery for ONSM treatment, however 3D conformal methods cannot be recommended.